Bayesian Persuasion By Stress Test Disclosure - Wolfgang Gick; Thilo Pausch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper argues that stress tests encompassing the entire banking sector (macro stress tests) can be designed to improve welfare. We develop a multi-receiver framework of Bayesian persuasion to show that a banking supervisor can create value when he commits to disclose the stress-testing methodology (signal-generating process) together with the stress test result (signal). By optimally choosing the two signals, supervisors can deliver superior information that will deliver a higher expected utility to prudent investors when acting accordingly. The paper uses an equilibrium construction with a continuum of receivers. We find that banking supervisors create welfare as optimal disclosure reduces uncertainty and leads to better risk-adjusted behavior on the investors' side and to less financial market volatility.
Keywords: D81; D84; G28; 330